2015
DOI: 10.1111/jbi.12660
|View full text |Cite
|
Sign up to set email alerts
|

Soil microorganisms behave like macroscopic organisms: patterns in the global distribution of soil euglyphid testate amoebae

Abstract: Aim Patterns of α‐ and β‐diversity of soil protist communities and the factors that shape them remain largely unknown. We undertook a world‐wide survey of forest litter to investigate the patterns of diversity in a group of testate amoebae. We aimed to assess: (1) whether there is a latitudinal gradient in α‐diversity, and (2) whether β‐diversity was correlated solely with environmental factors commonly used in soil biology research or if it was also independently explained by geographical barriers. Location W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 86 publications
2
39
0
Order By: Relevance
“…Our results show that microbial eukaryote total richness did not change with latitude (Table ) and did not differ significantly between Patagonian and Antarctic lakes (Table ). This contrasts with the prevailing general view of decreasing richness with latitude (Pianka, ; Gaston and Blackburn, ; Hillebrand, ) also observed in soil protists (Lara et al ., ), although there are a number of exceptions for aquatic (e.g. Crow, ; Passy, ) and soil (Fernández et al ., ) eukaryotic microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that microbial eukaryote total richness did not change with latitude (Table ) and did not differ significantly between Patagonian and Antarctic lakes (Table ). This contrasts with the prevailing general view of decreasing richness with latitude (Pianka, ; Gaston and Blackburn, ; Hillebrand, ) also observed in soil protists (Lara et al ., ), although there are a number of exceptions for aquatic (e.g. Crow, ; Passy, ) and soil (Fernández et al ., ) eukaryotic microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…A PCA (Appendix S2) confirmed water and energy variables as primary predictors of testate amoeba richness in SSA, though it also showed that the observed unimodal response to water and energy availability is not easy to separate from other socalled drivers of diversity such as (plant) productivity. Water and energy are undoubtedly essential for physiological processes in testate amoebae (Sch€ onborn, 1962) and have direct effects on their growth, survival and reproductive success (Laminger, 1978;Laybourn & Whymant, 1980), as well as on their abundance, diversity and distribution at large spatial scales (Wilkinson, 1994;Bates et al, 2013;Lara et al, 2016;present study). This calls for attention, especially when attempting to determine whether the reason behind the observed climate-richness links is physiologically based water-energy balance or trophically based productivity (Hawkins et al, 2003).…”
Section: Figurementioning
confidence: 99%
“…That is, as traits of a given species determine whether or not they can colonize new habitats, the community structure of an ecosystem is closely related to its spatial configuration. Despite the long‐standing but contested claim that unicellular organisms are only driven by local environmental filters due to large population densities and highly efficient dispersal (Finlay, ), major advances have been made indicating the importance of both niche and dispersal‐assembly theories in explaining the spatial distributions of micro‐organisms in aquatic and terrestrial systems (Barberán & Casamayor, [bacteria]; Viana et al., [microcrustaceans]; Moresco et al., [phytoplankton]; Heino et al., [diatoms]; Lara, Roussel‐Delif, Fournier, Wilkinson, & Mitchell, [testate amoeba]).…”
Section: Introductionmentioning
confidence: 99%